The Implementation of Kitab Kuning Learning in Indonesian Islamic Boarding Schools: A Comparison between the Traditional Sorogan Method and Digital-Based Innovations - Ichsan, Rozaq Shohibul; Khoiroh, Hani’atul; Makinuddin, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The study of yellow books is a treasure trove of classical Islamic knowledge and has served as the hallmark and primary identity of Islamic boarding schools education in Indonesia for centuries. Amidst the rapid development of technology and the emergence of a "digital native" generation, Islamic boarding schools now face inherent challenges in maintaining the tradition of classical methodology while embracing educational innovation. In this case, the author uses a literature review method with the aim of analyzing and comparing the implementation of yellow books learning using the traditional sorogan method with digital-based innovation methods. By analyzing four primary documents (three theses and one indexed journal article from 2012 – 2024), this study found that the sorogan method implemented at the Al-Munawwaroh Kepahiang and Miftahul Ulum Malang Islamic Boarding Schools has significant advantages in fostering depth of understanding, a sense of responsibility, and direct interaction between students and kyai, although it is constrained by the need for high time and patience. In contrast, the digital approach developed by Islamic Boarding School students at IAIN Bone offers acfcessibility, flexibility, and collaboration across time, but still requires intensive digital literacy mentoring. Student oriented Islamic boarding schools like Ibnu Katsir 2 in Jember demonstrate a hybrid model that integrates both. This study concludes that neither approach is absolutely superior; sorogan remains the lifeblood of character formation and depth of interpretation, while digital technology provides an inclusive solution in the millennial era. The primary recommendation is the development of a blended learning model for the yellow book (kitab kuning) that combines the power of sorogan with an open digital platform.